ANALISIS PERAN GURU DALAM MEMBINA ETIKA PENGGUNAAN ARTIFICIAL INTELLIGENCE PADA SISWA (STUDI KASUS DI SMA NEGERI 14 MUARO JAMBI) - Annisa Dwi Karisma; Ridwan Santoso; Muhammad Ichsan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The advancement of modern technology, especially Artificial Intelligence (AI), has brought major changes in the world of education, but the reality in the field shows a tendency for students to copy and paste from AI without verifying book sources, as well as minimal teacher guidance in utilizing this technology. This study aims to explore the role of teachers in fostering ethical use of AI in students at SMA Negeri 14 Muaro Jambi while identifying factors that influence the optimization of the role of teachers in fostering AI ethics. This study uses a qualitative approach with a case study research type. Data were collected through observation, interviews and documentation. The results of the study revealed that fostering ethical use of AI in SMA Negeri 14 Muaro Jambi has begun to be integrated through directions, reprimands, and instilling the values ​​of honesty and responsibility to make AI merely a learning tool. However, the implementation has not been optimal because students still often use AI instantly without understanding the material. From the teacher's perspective, the main obstacles faced include the lack of special training on the use of AI, limited teaching time amidst the dense demands of the curriculum, and challenges in low student literacy. This crucial obstacle was also emphasized by the Vice Principal for Student Affairs, that the fundamental problem does not lie in the age of the teachers or internet facilities, but rather in the lack of in-depth guidance.